EVALUASI DAN STRATEGI PENGEMBANGAN DESA WISATA DI KABUPATEN BADUNG, BALI - Hari Nalayani, Ni Nyoman Ayu (Jurnal Master Pariwisata (JUMPA), 2016)
Badung Regency, Bali Province, has eleven tourism villages which were established by Regulation of Badung Regent in 2010. The development level of the eleven tourism villages is different, therefore it needs to be evaluated so that the tourism village can be realized for the sake of balanced and sustainable development of tourism, especially in Central and North Badung. The purpose of this research was grouping the potential of each tourism village, grouping them based on the level of development, and formulating a plan of development strategies of each group of tourism villages in Badung Regency. This study used the theory of planning, sustainable tourism theory, the theory of community-based tourism and alternative tourism theory. The research method used quantitative and qualitative methods, then the analysis used a three rating scale method for classifying eleven tourism villages and SWOT analysis was used to formulate of tourism village development strategy plan in Badung regency.
Keywords: Evaluation; strategy development; tourism villages; Badung regency